Teacher Support Adaptivity in Physics Classroom for Gifted Students - Ayık, Zekai; Gül, Muhammet Davut (Universitas Negeri Semarang, 2025)
Gifted students have varying learning characteristics and learning needs. In this respect, adapted support to their skills and learning characteristics during academic activities plays a key role in engaging in learning activities and achieving learning goals. Accordingly, this study focuses on teachers' support of adaptivity competencies during microteaching from the perspective of both gifted and nongifted students. To this end, a descriptive comparative method was adopted, and gifted (n=124) and non-gifted (n=205) students joined the study. An adapted version of the Questionnaire on Teachers’ Support Adaptivity was employed for collecting data. Data were quantitatively analysed including MANOVA and ANOVA. The results revealed that both groups perceived the support they received from teachers as slightly above and below average, meaning that teachers were not competent. In deep analysis, results indicated a significant difference between the two groups, but no difference between girls and boys. That is, gifted students are more disadvantaged than nongifted students since their teachers lack strategies in adapting their support to meet the different academic needs of their students. This study recommends that teachers need pre-service or in-service training to offer quality and appropriate support for gifted students, which is crucial in achieving learning goals.